2020
DOI: 10.1021/acsnano.0c06280
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence and Electroluminescence of J-Aggregated Polythiophene Monolayers on Hexagonal Boron Nitride

Abstract: The photophysics of a semiconducting polymer is manipulated through molecular self-assembly on an insulating surface. Adsorption of polythiophene (PT) monolayers on hexagonal boron nitride (hBN) leads to a structurally induced planarization and a rebalancing of inter- and intrachain excitonic coupling. This conformational control results in a dominant 0–0 photoluminescence peak and a reduced Huang–Rhys factor, characteristic of J-type aggregates, and optical properties which are significantly different to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
(161 reference statements)
0
9
0
Order By: Relevance
“…hBN is also a promising template for the growth/deposition of other functional materials, such as GaN, VO 2 , Fe 3 O 4 , and polythiophene. [14][15][16][17] It can also work as a release layer which assists the transfer from the growth substrates to other substrates. 18 Stanene, a 2D form of Sn analogous to graphene and silicene which shows unique linear band dispersion, was also grown on hBN.…”
Section: Introductionmentioning
confidence: 99%
“…hBN is also a promising template for the growth/deposition of other functional materials, such as GaN, VO 2 , Fe 3 O 4 , and polythiophene. [14][15][16][17] It can also work as a release layer which assists the transfer from the growth substrates to other substrates. 18 Stanene, a 2D form of Sn analogous to graphene and silicene which shows unique linear band dispersion, was also grown on hBN.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kerfoot et al observed 4.5−6 times stronger 0−0 than 0−1 peak from planarly assembled poly(3-decylthiophene-2,5-diyl) (P3DT) lamellae on the hBN surface under 405 nm illumination. 43 With an interchain distance of ∼2.0 nm, they found that J-type fluorescence could be realized by the side-chain stacking thiophene lamella, which was very similar to our side-chain stacking NWs. Compared to their results, we would suggest two possible ways to further investigate the spectroscopic properties of different P3HT NWs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This indicates the formation of the planar stacking of P3HT in the middle region of the low/wide NWs. Planar stacking of P3HT is only observed as two-dimensional (2D) lamella with a height of 0.33 nm on graphite , and hexagonal boron nitride (hBN) surfaces. , The monolayer height of 2D lamella suggests that the P3HT chains are attached flatly to the surface. The ordered lamella was formed by the strong epitaxial effects, i.e., vdW interaction between the hexyl side chains and atomically ordered surfaces.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Polythiophene (PT) and its derivatives are very promising conducting polymers due to their numerous remarkable properties such as environmental and thermal stability [1][2][3], high electrical conductivity [4][5][6] and interesting electronic and optical characteristics [7][8][9][10]. Thanks to these features, polythiophene offers several industrial applications in various fields, including electronic devices such as transistors [11][12][13], organic light-emitting diodes (OLEDs) [14,15], photovoltaic cells [16][17][18][19], electrochromic devices [20,21] and sensors [22][23][24].…”
Section: Introductionmentioning
confidence: 99%